Capital Market Consequence of Institutional Investment Constraint: Evidence from the Stock Price Crash Risk in China. Issue 3 (3rd July 2022) - Fan, Yunqi; Hu, Guanglei
ABSTRACT: This study finds that institutional investment constraint increases stock price crash risk. We employ both instrumental variable approach and a quasi-experiment to identify the causal effect. We also find institutions are more likely to sell stocks with stronger institutional investment constraint in response to firm's bad news. In addition, the positive relationship between institutional investment constraint and crash risk is less pronounced for institutions of larger size and better past performance. These results are consistent with managerial catering explanation rather than career concern and soft information explanations. Finally, the channel analysis shows that the effect of institutional investment constraint on crash risk is mediated by predatory selling and investor information competition.